Cucurbitane-type triterpenoids from the vines of Momordica charantia and their anti-inflammatory, cytotoxic, and antidiabetic activity. (March 2022) - Liaw, Chia-Ching; Huang, Hung-Tse; Liu, Hui-Kang; Lin, Yu-Chi; Zhang, Li-Jie; Wei, Wen-Chi; Shen, Chien-Chang; Wu, Chia-Lun; Huang, Chung-Yi; Kuo, Yao-Haur
Abstract: Phytochemical investigation of the ethanol extract from wild Momordica charantia vines has resulted in isolation of seven cucurbitane-type triterpenoids, including six undescribed compounds, kuguaovins H‒M, and the known compound, momordicoside K. The structures of the isolated compounds were elucidated on the basis of spectroscopic analyses, including 1D and 2D NMR, and MS experiments. The chemical structure of momordicoside K was determined for the first time by X-ray crystallographic analysis and its absolute configuration assigned. The cytotoxicity against four human tumor cell lines and anti-inflammatory activities on LPS-stimulated RAW264.7 macrophages were evaluated. Of the isolates, kaguaovin L exhibited potential cytotoxicity against MCF-7, HEp-2, Hep-G2, and WiDr cancer cell lines and showed moderate anti-NO production activity. In addition, kuguaovins H and J also showed the stimulatory effect of GLP-1 secretion on the murine intestinal secretin tumor cell line (STC-1). Graphical abstract: Cucurbitane-type triterpenoids from Momordica charantia vines were established by NMR, HRESIMS, and single-crystal X-ray spectroscopic data and evaluated their bioactivities. Image 1 Highlights: Seven cucurbitane-type triterpenoids, including six undescribed ones, were isolated from the vines of wild Momordica charantia. The structures of the isolates were determined by spectroscopic data, especially 2D NMR, HRESIMS and single-crystal X-ray diffraction. Compounds 1 and 3 exhibited stimulatory effect of GLP-1 secretion on the murine intestinal secretin tumor cell line, while 4 exhibited anti-NO production and antiproliferative effects.